From Truman to Reagan: The Evolution of U.S. Nuclear Policy in the Cold War Context - Antidze, Maia (European Scientific Journal, ESJ, 2025)
Since the beginning of the nuclear era, the United States’ nuclear policy has exerted substantial influence on international security and the intricacies of the Cold War. This scholarly work analyzes the evolution of United States nuclear policy throughout the Cold War period, from the presidency of Harry Truman to that of Ronald Reagan. Ranging from President Harry Truman’s decisive deployment of atomic weapons to President Ronald Reagan’s dedication to modernization and arms reduction, successive administrations have adapted their strategic approaches in response to emerging threats, technological advancements, and changing diplomatic contexts. This paper offers a comprehensive qualitative analysis of the progression of U.S. nuclear policy from 1945 to 1988, scrutinizing presidential doctrines, arms control negotiations, and the persistent tension between deterrence and disarmament. The study synthesizes primary and secondary sources to underscore pivotal moments and strategic shifts, considering both American and Soviet perspectives. The research illustrates how nuclear policy has both influenced and reflected broader transformations in U.S. grand strategy, culminating in landmark treaties that contributed to the termination of the Cold War.